Analysis of the Effect of Intellectual Intelligence (IQ), Emotional Intelligence (EQ) And Spiritual Intelligence (SQ) on Employee Performance at PT Bank BTN (Persero) Tbk. Medan Branch - Betniar PURBA; Robinson SIPAHUTAR; Errie MARGERY; Joana L. SARAGIH (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to determine the effect of intellectual intelligence, emotional intelligence and spiritual intelligence on employee performance. The research method used was quantitative, with 60 respondents who were taken using proportionate stratified random sampling. The analysis technique used in this study is multiple linear regression and hypothesis testing. From the results of partial testing that intellectual intelligence has a positive and significant partial effect on employee performance. Emotional intelligence has a positive and not significant effect partially on employee performance. Spiritual intelligence has a positive and significant effect partially on employee performance. The coefficient of determination is 0.834 meaning that employee performance can be explained by the variables of intellectual intelligence, emotional intelligence and spiritual intelligence of 83.4% while another 16.6% is explained by other variables such as motivation and work discipline.